The Influence of Counseling by Midwife Towards the Selection of Aid and Delivery Place in the Work Area of Public Health Center Sitiung 1, Dharmasraya Regency - Evin Noviana Sari; Rati Purwati; Siti Khotimah (Science Midwifery, 2022)
This research is quasi-experimental research. The research subjects were 102 third trimester pregnant women who met the inclusion criteria. Data on counseling, birth attendant, place of delivery, education, knowledge, questionnaire. Data analysis was carried out using the Stata 8 program with statistical tests using McNemar to select variables that had a significant effect (p<0.05). The results of McNemar's analysis showed that there was a significant difference (p<0.05) between the counseling variable and the decision of pregnant women to choose a birth attendant, but counseling showed no significant difference (p>0.05) with the decision of pregnant women to choose the place of delivery. The choice of birth attendant after counseling 97% to health workers and 3% to non-health workers. While the choice of place of delivery after counseling, 91% chose to go to a health facility and 9% chose at home. Maternal education was not significantly related (p>0.05) with counseling and pregnant women's decisions in choosing birth attendants. Maternal education was not significantly related (p>0.05) with counseling and pregnant women's decision to choose the place of delivery. Mother's knowledge was significantly related (p<0.05) with counseling but not significantly (p>0.05) the decision of pregnant women to choose birth attendants. Mother's knowledge was not significantly related to counseling (p>0.05) and not significantly related (p>0.05) to the decision of pregnant women to choose the place of delivery